Imitator of signals for plan-position indicator «Picket» - Tsevuch, I. V.; Sheik-Seikin, A. M.; Sadchenko, A. V.; Kushnirenko, O. A.; Savchuk, Yu. O. (Technology and design in electronic equipment, 2017)
The authors have developed a device for imitation of the signal-interference environment for radars, equipped with the plan-position indicator (PPI) «Picket», which does not require a PC for operation. Thanks to the use of the original method of forming marks from targets, it was possible to significantly reduce the amount of memory, required to store information about the scenario that reliably imitates the operation of the radar in real conditions. The device provides simultaneous operation of twelve indicators of a circular survey and is intended for equipping training centers for the training of air control operators.